Korelasi Pengetahuan dengan Perilaku Pasien dalam Penggunaan NSAIDs untuk Swamedikasi Nyeri di Apotek - Zainul Islam; Lulu Isra Safira (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The use of drugs for self-medication without proper knowledge and behavior can have a negative impact. This study explores the relationship between knowledge and behavior of patients self-medicating for pain at Serang City pharmacies. This study adopted cross-sectional research and sampling using purposive sampling. The level of knowledge and behavior was assessed using a questionnaire. This study included a total of 222 respondents (age 18-59 years) who were using non-steroidal anti-inflammatory drugs (NSAIDs) for pain and had taken them for the previous 3 months. The analysis of the relationship between knowledge and behavior was measured using the Spearman rho test. The results of showed a sufficient level of knowledge of the respondents (59.9%) with responsible behavior (57.2%). Spearman rho correlation test showed that there is a significant relationship between knowledge and behavior with a fairly strong correlation value (r = 0.715) in a positive direction. The higher the knowledge in self-medication, the better the behavior will be.